Cochlea-Specific Deletion of Cav1.3 Calcium Channels Arrests Inner Hair Cell Differentiation and Unravels Pitfalls of Conditional Mouse Models - Eckrich, Stephanie; Hecker, Dietmar; Sorg, Katharina; Blum, Kerstin; Fischer, Kerstin; Münkner, Stefan; Wenzel, Gentiana; Schick, Bernhard; Engel, Jutta (Frontiers in Cellular Neuroscience, 2019)
Inner hair cell (IHC) Cav1.3 Ca2+ channels are multifunctional channels mediating Ca2+ influx for exocytosis at ribbon synapses, the generation of Ca2+ action potentials in pre-hearing IHCs and gene expression. IHCs of deaf systemic Cav1.3-deficient (Cav1.3-/-) mice stay immature because they fail to up-regulate voltage- and Ca2+-activated K+ (BK) channels but persistently express small conductance Ca2+-activated K+ (SK2) channels. In pre-hearing wildtype mice, cholinergic neurons from the superior olivary complex (SOC) exert efferent inhibition onto spontaneously active immature IHCs by activating their SK2 channels. Because Cav1.3 plays an important role for survival, health and function of SOC neurons, SK2 channel persistence and lack of BK channels in systemic Cav1.3-/- IHCs may result from malfunctioning neurons of the SOC. Here we analyze cochlea-specific Cav1.3 knockout mice with green fluorescent protein (GFP) switch reporter function, Pax2::cre;Cacna1d-eGFPflex/flexand Pax2::cre;Cacna1d-eGFPflex/-. Profound hearing loss, lack of BK channels and persistence of SK2 channels in Pax2::cre;Cacna1d-eGFPflex/- mice recapitulated the phenotype of systemic Cav1.3-/- mice, indicating that in wildtype mice, regulation of SK2 and BK channel expression is independent of Cav1.3 expression in SOC neurons. In addition, we noticed dose-dependent GFP toxicity leading to death of basal coil IHCs of Pax2::cre;Cacna1d-eGFPflex/flex mice, likely because of high GFP concentration and small repair capacity. This and the slower time course of Pax2-driven Cre recombinase in switching two rather than one Cacna1d-eGFPflex allele lead us to study Pax2::cre;Cacna1d-eGFPflex/- mice. Notably, control Cacna1d-eGFPflex/- IHCs showed a significant reduction in Cav1.3 channel cluster sizes and currents, suggesting that the intronic construct interfered with gene translation or splicing. These pitfalls are likely to be a frequent problem of many genetically modified mice with complex or multiple gene-targeting constructs or fluorescent proteins. Great caution and appropriate controls are therefore required.